The power of the sea : tsunamis, storm surges, rogue waves, and our quest to predict disasters - Parker, Bruce B. (New York : Palgrave Macmillan, 2010)
"Classics from Moby Dick to A Perfect Storm have sought to capture mankind's obsession with the might and the mystery of the sea. And the greatest minds for centuries, including Isaac Newton, Napoleon, and Benjamin Franklin, have worked to understand and predict when its next act of destruction will occur. The awesome power of the earth's oceans have been at the forefront of everyone's minds in recent years, from the 2004 Indian Ocean Tsunami (230,000 dead) to the devastation of New Orleans after Hurricane Katrina to the unknown consequences of the melting of thousands of glaciers as the Earth's temperature slowly rises. Bruce Parker, former Chief Scientist for the National Ocean Service, brings together the breathtaking history of man's relationship with the sea with the latest scientific breakthroughs to explore in this wide-sweeping, fascinating narrative"--
When the sea turns against us : escaping the sea's fury through prediction -- The earliest predictions for the sea : the tide -- The moon, the sun, and the sea : the tide predictions for D-Day -- The sea's greatest killer : predicting storm surges -- Defending our coasts : flooded cities -- Stormy seas : predicting sea, swell, and surf -- "Holes" in the surface of the sea : rogue waves -- The sea;s response to an unpredictable Earth : trying to predict tsunamis -- December 26, 2004 (part 1) : tragic surprise in the Indian Ocean -- December 26, 2004 (part 2) : learning from a tragedy -- Predicting the future-- and saving lives : El Niño, climate change, and the Global Ocean Observing System.
Includes bibliographical references (p. [225]-284) and index.
Keywords: Oceanography; Ocean and civilization